Cardiovascular immunotoxicities associated with immune checkpoint inhibitors: a safety meta-analysis. (16th September 2021) - Dolladille, Charles; Akroun, Julia; Morice, Pierre-Marie; Dompmartin, Anne; Ezine, Emilien; Sassier, Marion; Da-Silva, Angélique; Plane, Anne-Flore; Legallois, Damien; L'Orphelin, Jean-Mathieu; Alexandre, Joachim
Abstract: Aims : The risk and incidence of cardiovascular (CV) immune-related adverse events (irAEs) associated with immune checkpoint inhibitors (ICIs) in cancer patients remain unknown. Methods and results: We systematically reviewed all randomized clinical trials (RCTs) including at least one ICI-containing arm and available CV adverse event (CVAE) data in cancer patients in the ClinicalTrials.gov registry, Medline, and the Cochrane CENTRAL Register of Controlled Trials, up to 31 August 2020 (CRD42020165672). The primary outcome was the summary risk of 16 different CVAEs associated with ICI exposure vs. controls (placebo and non-placebo) in RCTs. CVAEs with an increased risk associated with ICI exposure were considered as CV irAEs. Summary incidences of CV irAEs identified in our primary outcome analyses were computed using all RCTs including at least one ICI-containing arm. We used a random-effects meta-analysis to obtain Peto odds ratios (ORs) with 95% confidence intervals (CIs) and logit transformation and inverse variance weighting to compute summary incidences. Sixty-three unique RCTs with at least one ICI-containing arm (32 518 patients) were retrieved, among which 48 (29 592 patients) had a control arm. Among the 16 CVAEs studied, ICI use was associated with an increased risk of 6 CV irAEs including myocarditis, pericardial diseases, heart failure, dyslipidemia, myocardial infarction, and cerebral arterial ischaemia with higher risks for myocarditis (Peto OR: 4.42, 95% CI: 1.56–12.50, P  < 0.01; I 2 = 0%, P  = 0.93) and dyslipidemia (Peto OR: 3.68, 95% CI: 1.89–7.19, P  < 0.01; I 2 = 0%, P  = 0.66). The incidence of these CVAEs ranged from 3.2 (95% CI 2.0–5.1) to 19.3 (6.7–54.1) per 1000 patients, in studies with a median follow-up ranging from 3.2 to 32.8 months. Conclusion: In RCTs, ICI use was associated with six CV irAEs, not confined to myocarditis and pericarditis. Graphical Abstract: